Determination of 14 Benzodiazepine Multiresidues in Aquaculture Environment by Ultra-High-Performance Liquid Chromatography–Tandem Mass Spectrometry - Hongyang Guo; Jianwu Chen; Guangjun Jiang; Yuqing Mei; Zhiqiang Gong; Mingdian Liu; Jinping Li; Jinhua Gan (Molecules)
In this study, an analytical method for the simultaneous determination of 14 benzodiazepine (BDZ) multiresidues in aquaculture environmental water and sediment was developed using ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC-MS/MS). The method uses an internal standard for quantification and achieves chromatographic separation and analysis within 11 min. The results of method validation showed that the recoveries of most analytes were in the range of 70–120% in water or sediment matrices, and the correlation coefficients of the 14 target chemistries were R2 > 0.99, with relative standard deviations (RSD) < 15%. The limits of detection (LODs) and the limits of quantification (LOQs) were in the ranges of 0.002–0.01 μg/L and 0.01–0.03 μg/L for water and 0.01–0.5 μg/kg and 0.04–1 μg/kg for the sediment matrix. The method is simple and has high rapidity, high sensitivity, and low cost. It provides technical support for the simultaneous monitoring of BDZ residues in the aquaculture environment.